Mood and equity pricing - Dowling, Michael Mark (Trinity College (Dublin, Ireland). Trinity Business School, 2007)
This thesis investigates the theoretical and empirical relationship between mood and equity pricing. The theoretical relationship is explored by reference to the relevant psychological, decision-making, behavioural economics, and behavioural finance research. The empirical relationship is explored through the robust testing of a variety of variables that are argued to proxy for mood against a wide range of national indices and US sub-indices.
Keywords: Business, Ph.D.; Ph.D. Trinity College Dublin